Isolation and Identification of Antibacterial and Antifungal Compounds from Praxelis clematidea R. M. King & H. Robinson as an Effective Potential Treatment against Rice Pathogens - Cuong C. Nguyen (MDPI AG, 2021)
Bacterial leaf blight and blast diseases caused by the bacterium Xanthomonas oryzae pv. oryzae and the fungus Pyricularia oryzae, respectively, are among the most important infectious diseases affecting rice. We evaluated the antimicrobial effects of compounds derived from Praxelis clematidea on Xanthomonas oryzae and Pyricularia oryzae. The dried aerial parts of Praxelis clematidea were subjected to ethanol extraction, separated by solvent partitioning using hexane, chloroform, ethyl acetate, and water. In vitro assays demonstrated that the main antibacterial and antifungal activities were distributed in the ethyl acetate and chloroform fractions, respectively. These fractions were further separated using silica gel chromatography and reversed-phase chromatography. Finally, we isolated five compounds, 1–5, that inhibited the growth of Xanthomonas oryzae in vitro and four compounds, 6–9, that exhibited in vitro antifungal activity against Pyricularia oryzae. We evaluated their antimicrobial activities and identified their chemical structures by NMR and mass spectrometry analyses. This is the first study to isolate compound 2 (4,4′,4″-nitrilotriphenol) as an alternative microbial from natural resources and evaluate its physiological activity. Moreover, this is the first report to demonstrate antibacterial activity in comparison with flavonoids. Praxelis clematidea extracts plausibly exert both antibacterial and antifungal effects, which should be further validated in field trials.